Analise da influencia de fatores ambientais na estimativa da evapotranspiração em área de floresta na Amazônia - GALVÃO, Welde Moraes (2019)
The performance of methods estimates of evapotranspiration using only air temperature as the only environmental forcing (Thorntwaite, Silva and Linacre), and those that use air temperature and solar radiation (Camargo, Hargreaves-Samani and Jensen-Haise) in relation to the method Penmam in the area of tropical forest were analyzed in this study, in order to evaluate the real influence of environmental factors, air temperature and solar radiation in the complex and dynamic transfer of vapor in the soil-atmosphere interface. The study was conducted in the Research Station Ferreira Pena (ECFPn), located in the forest reserve Caxiuanã (01º 44´ 35´´ S; 051º 27´ 22´´ W), west of the State of Pará. The meteorological data used were: average temperature, maximum and minimum air, solar radiation, relative humidity, evaporation of tar and vapor pressure deficit of air, referring to a period of four years (1996-1999). The values estimated by the method of Penmam methods were compared with those who base their estimates only on the influence of air temperature, along with those that are based on the simultaneous influence of solar radiation and air temperature. The comparison of the estimates were validated using simple statistical test such as coefficient of determination, slope (a) and linear (b) of the linear regression test error estimates (mean and mean relative error) and accuracy rate (r). The results showed that the Hargreaves-Samani methods and Jansen-Haise (which combine the influence of solar radiation and air temperature in the estimates of evaportanspiração) showed the best correlation with Penman, with (R2 = 0.96 and R2 = 0.96) respectively. Another finding is that the air temperature and solar radiation are very important climatic factors for the realization of the process evapotranspiratório, but not the only ones.